Ethanol Extract of Oldenlandia diffusa - an Effective Chemotherapeutic for the Treatment of Colorectal Cancer in Humans -Anti-Cancer Effects of Oldenlandia diffusa- - Soojin Lee; Ji Hwan Shim; Huijin Gim; Hyun Soo Park; Byung Joo Kim (Korean Pharmacopuncture Institute, 2016)
Objectives: Oldenlandia diffusa is traditionally used to relieve the symptoms of and to treat various diseases, but its anti-cancer activity has not been well studied. In the present study, the authors investigated the anti-cancer effects of an ethanol extract of Oldenlandia diffusa (EOD) on HT-29 human adenocarcinoma cells. Methods: Cells were treated with different concentrations of an EOD, and cell death was assessed by using a 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. Analyses of the sub G1 peak, the caspase-3 and -9 activities, and the mitochondrial membrane depolarizations were conducted to confirm cell death by apoptosis. Also, intracellular reactive oxygen species (ROS) generation was determined using carboxy-H2DCFDA (5-(and-6)-carboxy-20,70-dichlorodihydrofluorescein diacetate). Results: EOD inhibited the proliferation of HT-29 cells for 24 hours by 78.6% ± 8.1% at 50 μg/mL, 74.4% ± 4.6% at 100 μg/mL, 65.9% ± 5.2% at 200 μg/mL, 51.4% ± 6.2% at 300 μg/mL, and by 41.7% ± 8.9% at 400 μg/mL, and treatment for 72 hours reduced the proliferation at the corresponding concentrations by 43.3% ± 8.8%, 24.3 ± 5.1 mV, 13.5 ± 3.2 mV, 6.5 ± 2.3 mV, and by 2.6 ± 2.3 mV. EOD increased the number of cells in the sub-G1 peak in a dose-dependent manner. The mitochondrial membrane depolarization was elevated by EOD. Also, caspase activities were dose-dependently elevated in the presence of EOD, and these activities were repressed by a pan-caspase inhibitor (zVAD-fmk). The ROS generation was significantly increased by EOD and N-acetyl-L-cysteine (NAC; a ROS scavenger) remarkably abolished EOD-induced cell death. In addition, a combination of sub-optimal doses of EOD and chemotherapeutic agents noticeably suppressed the growth of HT-29 cancer cells. Conclusion: These results indicate that EOD might be an effective chemotherapeutic for the treatment of human colorectal cancer.